👤

Aider moi svp URGENT
Exercice 1: développer les expressions suivante
À(x)=-7(3-5x) B(x)=9x(-7x-2)
Exercice 2: développer puis réduire
À(x)=5(2x+1)+3(x+7) B(x)=-2x(3x+7)-(6x au carré -3x)
Merci beaucoup


Répondre :

Bonjour,

Exercice 1: développer les expressions suivantes
À(x)=-7(3-5x)
A (x) = - 21 + 35x
A (x) = 35x - 21

B(x)=9x(-7x-2)
B (x) = - 63x² - 18x

Exercice 2: développer puis réduire 
À(x)=5(2x+1)+3(x+7)
A (x) = 10x + 5 + 3x + 21
A (x) = 13x + 26

B(x)=-2x(3x+7)-(6x² -3x)
B (x) = - 6x² - 14x - 6x² + 3x
B (x) = - 12x² - 11x